1998
DOI: 10.1111/j.1600-051x.1998.tb02390.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between salivary calcium and oral health

Abstract: Recently, we have shown positive correlations between high salivary calcium content and periodontitis, and between high salivary calcium level and the number of intact teeth in selected groups of subjects. The aim of our present study was to determine whether these correlations could be seen in a randomized group of healthy adults. A thorough oral examination including orthopantomograms was carried out for a total of 137 healthy subjects, 63 men (35.4+/-5.6 years) and 74 women (33.2+/-4.7 years). Paraffin-stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
42
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 18 publications
7
42
0
3
Order By: Relevance
“…In our view, increased salivary Ca stems from a shift of plasma calcium through the injured mucosa. The plasma concentration of Ca is a plausible source of salivary Ca in damaged mucosa, as previously demonstrated by Sewon et al (14), who reported a positive correlation between gingival bleeding and Ca in saliva. In this study we have seen a very significant increase Table 1.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In our view, increased salivary Ca stems from a shift of plasma calcium through the injured mucosa. The plasma concentration of Ca is a plausible source of salivary Ca in damaged mucosa, as previously demonstrated by Sewon et al (14), who reported a positive correlation between gingival bleeding and Ca in saliva. In this study we have seen a very significant increase Table 1.…”
Section: Discussionsupporting
confidence: 48%
“…Electrolytes are known to be secreted in the mouth by the salivary glands, although the exudation of serum from injured oral mucosa also contributes to electrolyte concentrations found in saliva. In patients with SS, an increase has been documented in the rate of salivary albumin due to inflammation of the salivary glands and to the leakage of serum through mucous membranes easily damaged by mechanical action; this could equally be the mechanism that promotes salivary electrolyte abnormalities in SS (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the finding that walking patients had fewer secondary diagnoses and used fewer daily medications than those with poor mobility supports the view that in spite of the probably drug-related reduction in salivary flow (22), some other factors counteracted with the multitude of caries-inducing factors present in the oral cavity of physically inactive patients. One such factor could be a high level of salivary calcium, which has earlier been connected with low caries activity (23)(24)(25). Patients prone to osteoporosis seem to have higher levels of salivary calcium than their healthy controls (26)(27)(28).…”
Section: Discussionmentioning
confidence: 98%
“…Por el contrario, Kargul et al 15 no detectaron diferencias en la composición inorgánica de la saliva entre niños que presentaban o no caries. Otros autores 23 observaron correlación positiva entre altos niveles de calcio salival y el estado de salud dental y gingival. Respecto a la relación Ca/P, estudios realizados en niños de cuatro y cinco años por Cornejo et al 8 mostraron relación entre valores menores de Ca/P y el incremento de caries en un año de estudio.…”
Section: Discussionunclassified